The Role of Indoleamine-2,3-Dioxygenase in Cancer Development, Diagnostics, and Therapy - Hornyák, Lilla; Dobos, Nikoletta; Koncz, Gábor; Karányi, Zsolt; Páll, Dénes; Szabó, Zoltán; Halmos, Gábor; Székvölgyi, Lóránt (Frontiers in Immunology, 2018)
Tumors are composed of abnormally transformed cell types and tissues that differ from normal tissues in their genetic and epigenetic makeup, metabolism and immunology. Molecular compounds that modulate the immune response against neoplasms offer promising new strategies to combat cancer. Inhibitors targeting the indoleamine-2,3-dioxygenase 1 enzyme (IDO1) represent one of the most potent therapeutic opportunities to inhibit tumor growth. Herein we assess the biochemical role of IDO1 in tumor metabolism and immune surveillance, and review current diagnostic and therapeutic approaches that are intended to increase the effectiveness of immunotherapies against highly aggressive and difficult-to-treat IDO-expressing cancers.